AAC menu interface: Effectiveness of active versus passive learning to master abbreviation-expansion codes. - Gregory, Ellyn; Soderman, Melinda; Ward, Christy; Beukelman, David R.; Hux, Karen (AAC: Augmentative & Alternative Communication, 2006)
This study investigated the accuracy with which 30 young adults without disabilities learned abbreviation expansion codes associated with specific vocabulary items that were stored in an AAC device with two accessing methods: mouse access and keyboard access. Both accessing methods utilized a specialized computer application, called AAC Menu, which allowed for errorless practice. Mouse access prompted passive learning, whereas keyboard access prompted active learning. Results revealed that participants who accessed words via a keyboard demonstrated significantly higher mastery of abbreviation-expansion codes than those who accessed words via a computer mouse.